Safe in India: Casting light on the dark side of workers’ safety in the automotive industry - KOTHA, Reddi (Institutional Knowledge at Singapore Management University, 2024)
Set in 2023, the case documents the initiatives of the Safe in India Foundation (SII), a non-profit organisation, that aims to improve workers’ safety and social security in India’s automobile manufacturing industry. The issue is complex and multifaceted as the industry’s deep supply chain has many small and mid-sized factories comprising skilled and unskilled workers. SII’s four-pillar programme – supporting workers directly, improving workplace safety in the automotive sector through systemic change, improving healthcare and compensation policy at ESIC, and spreading awareness, especially by empowering workers through knowledge - attempts to foster a safety culture in the industry and among workers. In the six years since it was established, the signs of systemic change to improve worker safety have been noticed. However, SII’s leadership team wanted to scale the impact. For that, SII’s Co-Founder & Chief Executive Officer, Sandeep Sachdeva, had to consider the strategic options and trade-offs involving key stakeholders that included the automobile brands, the government, and workers, among others. By analysing the case, students would learn to identify commercial and social opportunities, understand the cognitive process spurring strategic actions, formulate a clear strategy and align actions towards achieving the mission, and evaluate and choose the strategic and funding options for their organisation.